2022
DOI: 10.22376/ijpbs/lpr.2021.11.3.l1-11
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Invitro Antioxidant, Anti-Inflammatory and Anticancer Activities of Limonia acidissima Fruits

Abstract: Wood apple botanically identified as Limonia acidissima is an indigenous fruit with amazing nutritional and health benefits. Reports from traditional literature of Ayurveda and Siddha portrays the medicinal properties of this fruit. The scooped pulp of the ripe fruit is consumed as such or it can be made into different recipes. But inclusion of this fruit in our diet is not found as a regular practice. Many people are still unaware of the benefits of this fruit. Hence, this study was taken up to unravel the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In the present study, the polyherbal formulation of Tulasi oil showed a maximum percentage of haemolysis at 250 μg/ml concentration (86%) which is lower than that of the standard (88%). Similarly, Sree et al, 30 proved that the anti-inflammatory potential of polyherbal formulation of Balapunarnavadi choornam by HRBC membrane stabilization Denaturation of tissue proteins is one of the underlying causes of inflammatory and arthritic disease 31 . Neutrophils are known to be a rich source of proteinases which carry in their lysosomal granules, and it was previously reported that leukocytes proteinase plays an important role in the development of tissue damage during the inflammatory response 32 .…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, the polyherbal formulation of Tulasi oil showed a maximum percentage of haemolysis at 250 μg/ml concentration (86%) which is lower than that of the standard (88%). Similarly, Sree et al, 30 proved that the anti-inflammatory potential of polyherbal formulation of Balapunarnavadi choornam by HRBC membrane stabilization Denaturation of tissue proteins is one of the underlying causes of inflammatory and arthritic disease 31 . Neutrophils are known to be a rich source of proteinases which carry in their lysosomal granules, and it was previously reported that leukocytes proteinase plays an important role in the development of tissue damage during the inflammatory response 32 .…”
Section: Discussionmentioning
confidence: 96%
“…The findings the study revealed the presence of higher phenolic content ranging from 3.01 to 7.23 mg GAE/g on DW [ 30 ]. A separate study found that wood apple fruit contains a total phenolic compound in the concentration of 32.18 μg/mg [ 16 ]. Kerkar et al [ 4 ] reveals that L. acidissima exhibits a significant level of phenolic content, measuring 38.67 mg (GAE)/g DW [ 4 ].…”
Section: Phytochemical Profilementioning
confidence: 99%
“…The extracts' flavonoid concentration was discovered to be extremely high ranging from 35.51 μg CE/mg [ 1 ]. A different study was conducted in which the total flavonoid content was estimated to be 18.15 μg/mg [ 16 ].…”
Section: Phytochemical Profilementioning
confidence: 99%
See 2 more Smart Citations